2013
DOI: 10.1016/j.jmarsys.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium in an ocean general circulation model compared with the West Atlantic Geotraces cruises

Abstract: International audienceA model of aluminium has been developed and implemented in an Ocean General Circulation Model (NEMO-PISCES). In the model, aluminium enters the ocean by means of dust deposition. The internal oceanic processes are described by advection, mixing and reversible scavenging. The model has been evaluated against a number of selected high-quality datasets covering much of the world ocean, especially those from the West Atlantic Geotraces cruises of 2010 and 2011. Generally, the model results ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 81 publications
3
77
0
Order By: Relevance
“…However, a recent comparison of thirteen Fe-incorporating GBMs found that 'all models struggle to reproduce many aspects of the observed spatial patterns' (Tagliabue et al, 2016). For other metals, such as Mn and Al, good agreement between observed and modeled values have been achieved in select parts of the global ocean (van Hulten et al, 2017(van Hulten et al, , 2014(van Hulten et al, , 2013. However, each GBM still struggles to replicate certain processes (e.g.…”
Section: Constraining the Particulate Export Of Trace Metalsmentioning
confidence: 99%
“…However, a recent comparison of thirteen Fe-incorporating GBMs found that 'all models struggle to reproduce many aspects of the observed spatial patterns' (Tagliabue et al, 2016). For other metals, such as Mn and Al, good agreement between observed and modeled values have been achieved in select parts of the global ocean (van Hulten et al, 2017(van Hulten et al, , 2014(van Hulten et al, , 2013. However, each GBM still struggles to replicate certain processes (e.g.…”
Section: Constraining the Particulate Export Of Trace Metalsmentioning
confidence: 99%
“…In regions where removal of dissolved metals by scavenging occurs at a much faster rate than transport by advection, ocean circulation is expected to contribute little to the overall uncertainty in dust deposition calculated from dissolved metal inventories [45,88]. In highly advective regimes, such as the eastern half of our study area under the influence of the North Equatorial Current [75], the dissolved metal distribution will be spatially smeared to a degree that may be quantifiable as biogeochemical modelling of dissolved trace element cycles improves.…”
Section: (I) Advection and Mixingmentioning
confidence: 99%
“…A critical factor limiting the use of dissolved Al inventories to quantify the supply of dust is the uncertainty of the dissolved Al residence time, including its sensitivity to spatial and temporal variability of biological productivity as well as the abundance and composition of particles that scavenge Al from the water column [45,53,88,89]. To illustrate this point, we calculate the residence time of dissolved Al in surface waters that would be implied by applying an assumed aerosol settling rate of 1000 m day −1 to the surface aerosol Al concentration measured along section GA03 ( §3a) and multiplying by each set of measured aerosol Al solubility results ( §3c).…”
Section: (Ii) Residence Timementioning
confidence: 99%
See 1 more Smart Citation
“…We closed all 24 PRISTINE samplers at the same depth near the bottom at 1015 m. The concentrations of DAl were similar in all 24 bottles with an average concentration of 17.41 ± 0.22 nM (Figure 7a). The concentrations of DFe were very similar in 22 out of 24 bottles with an average concentration of 1.029 ± 0.045 nM (bottles 2 & 18 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 , Al (Bruland et al, 2014;Middag et al, 2015;van Hulten et al, 2013), Hg (Lamborg et al, 2014), Co (Dulaquais et al, 2014) and the organic complexation of Fe . This confirms that the intended ultraclean performance of the PRISTINE samplers is excellent.…”
Section: Resultsmentioning
confidence: 99%